Comparative analysis of short-term outcomes between upper radical and total radical gastrectomy in patients with proximal gastric cancer - Alam, M. Reazul; Sayem, M. Abu; Yusuf Jamil, M. Abdullah; Alam, Mohammad Sahajadul; Islam, Nadia Farzana; Rahman, M. Shahinur; Rahman, Ashrafur (International Journal of Research in Medical Sciences, 2025)
Background: Gastric cancer remains a significant global health burden, ranking as the fifth most common cancer and the third leading cause of cancer-related deaths. Surgical interventions like Upper Radical Gastrectomy (URG) and Total Radical Gastrectomy (TRG) are pivotal in the management of proximal gastric cancer. This study aims to compare the short-term outcomes between URG and TRG in patients with proximal gastric cancer. To evaluate and compare the immediate postoperative outcomes, including complications, gastrointestinal (GIT) functionality, nutritional status, hospital stay duration and recovery between URG and TRG in patients with proximal gastric cancer. Methods: This prospective observational study was conducted on 67 patients diagnosed with operable proximal gastric cancer at the National Institute of Cancer Research & Hospital and National Gastro-liver Institute & Hospital, Dhaka. Results: The study found that URG patients generally had better short-term outcomes than those undergoing TRG. URG was associated with a lower rate of immediate postoperative complications (7.14% vs. 84.62% in TRG), shorter hospital stays, superior nutritional outcome and faster recovery of gastrointestinal functionality with significantly lower mean feeding time with higher incidence of post-operative bile reflux in URG group compared to TRG group. Additionally, TRG patients exhibited higher rates of lympho-vascular invasion and node involvement, necessitating a more radical surgical approach. Conclusions: URG may offer superior short-term outcomes compared to TRG in patients with proximal gastric cancer, particularly in terms of postoperative recovery and reduced complications.